New lectotypification of Crotalaria incana var. australis (Crotalarieae, Fabaceae): An example of procedure to determine the correct types from the Lorentz & Hieronymus collection - Planchuelo, Ana María; Espinar, Luis Ariza (Phytotaxa, 2015)
The first collections of Crotalaria incana from central Argentina were analyzed with special attention to specimens collected by P. Lorentz & G. Hieronymus housed at CORD, GOET, and SI (fragments ex CORD) that are syntypes of Crotalaria incana var. australis. The previous designation of P. Lorentz & G. Hieronymus 242 (CORD) as a lectotype is not correct as this sheet is not original material and therefore must be considered to be a neotype. Here we designate P. Lorentz & G. Hieronymus 242 (GOET) as the lectotype of the variety.